The Prognostic Value of Surgery in Treatment of Diverticular Colopathy: a propósito de 250 caos - Tato, Gladys; Somma, Caren; Bielawsky, Jorge; Bortagaray, Gustavo; de la Sovera, Margarita; Mate, Miguel (Cirugía del Uruguay, 1981)
Based on the analysis of 250 cases, the authors propose guidelines for the treatment of diverticular colopathies and point out factors of prognostic value in surgical treatment.